Effects of Environmental Enrichment on Stress and Welfare in Laboratory Animals - Charles, Sonia (Animal Health Journal, 2024)
Purpose: The general purpose of this study was to examine the effects of environmental enrichment on stress and welfare in laboratory animals. Methodology: The study adopted a desktop research methodology. Desk research refers to secondary data or that which can be collected without fieldwork. Desk research is basically involved in collecting data from existing resources hence it is often considered a low cost technique as compared to field research, as the main cost is involved in executive's time, telephone charges and directories. Thus, the study relied on already published studies, reports and statistics. This secondary data was easily accessed through the online journals and library. Findings: The findings reveal that there exists a contextual and methodological gap relating to the effects of environmental enrichment on stress and welfare in laboratory animals. Preliminary empirical review revealed that that enriching their living environments significantly improved their well-being. They found that interventions such as physical, social, cognitive, and sensory enrichment reduced stress levels, promoted natural behaviors, and enhanced cognitive function. Tailoring enrichment programs to specific species' needs and considering factors like environmental complexity and novelty proved crucial. Moreover, these interventions not only benefited animal welfare but also improved research outcomes by reducing stress and enhancing the validity of preclinical studies. Overall, the research underscored the importance of implementing evidence-based enrichment strategies to ensure the ethical treatment of laboratory animals and enhance the reliability of scientific research. Unique Contribution to Theory, Practice and Policy: The Biophilia Hypothesis, Optimal Stimulation theory and Stress Inoculation theory may be used to anchor future studies on stress and welfare in laboratory animals. The study made significant contributions to theory, practice, and policy in the field of laboratory animal welfare. It provided valuable insights into the underlying mechanisms of environmental enrichment's influence on animal well-being, contributing to existing theoretical frameworks such as the Biophilia Hypothesis, Optimal Stimulation Theory, and Stress Inoculation Theory. Additionally, the study offered practical recommendations for implementing evidence-based enrichment programs tailored to the needs of different animal species. These findings informed policy development by guiding the establishment of standards for enrichment in laboratory animal facilities, enhancing the protection and welfare of laboratory animals across institutional and national levels. Keywords: Environmental Enrichment, Laboratory Animals, Stress, Welfare, Mechanisms, Biophilia Hypothesis, Optimal Stimulation Theory, Stress Inoculation Theory, Implementation, Standards, Well-Being